O PAPEL DO DIRETOR DE ESCOLA FRENTE AOS NOVOS DESAFIOS DA GESTAO ESCOLAR - Ana Paula Maioli Martins; Cláudio Roberto Brocanelli (Universidade do Oeste Paulista, 2010)
This article aims to resume historical characteristics of school management in order to demonstrate its transformations according to the contexts and different times. To analyze fundamental issues in the context of the management school and the new challenges implicated to it, because of new demands that the school faces in the context of a society that is democratizing and turns. At a time when the world is undergoing major and quick changes, new positions are required, in front that, the school manager's role is crucial, and his is required new knowledge, attentions and abilities. So, although the survey is based in a theoreticalbibliographical study, seeks to understand why in many cases, the manager can not to transpose in practice what is already in his speech; and to investigate the historical origins of the principal's function, to understand the actual specificity of this professional activity and their main responsibilities.